2011
DOI: 10.1016/j.nimb.2011.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of ion beam analysis: Possibilities and limitations

Abstract: Quantitative application of ion beam analysis methods, such as Rutherford backscattering, elastic recoil detection analysis, and nuclear reaction analysis, requires the use of computer simulation codes. The different types of available codes are presented, and their advantages and weaknesses with respect to underlying physics and computing time requirements are discussed. Differences between different codes of the same type are smaller by about one order of magnitude than the uncertainty of basic input data, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…For the derived depth profiles roughness effects are interpreted as depth profiles of elements. Nevertheless, it has been already shown that in case of ambiguities between depth profiles and surface roughness the total amounts of elements are still correct even if the depth profiles may not reflect the sample structure correctly [12]. Optical microscopy of cross-sections shows that there are thick deposits on top of the original tile surface, and that the films have a multi-layered structure with some of the layers being less than 1 μm thick [7].…”
Section: 2deposition Pattern In the Divertormentioning
confidence: 99%
“…For the derived depth profiles roughness effects are interpreted as depth profiles of elements. Nevertheless, it has been already shown that in case of ambiguities between depth profiles and surface roughness the total amounts of elements are still correct even if the depth profiles may not reflect the sample structure correctly [12]. Optical microscopy of cross-sections shows that there are thick deposits on top of the original tile surface, and that the films have a multi-layered structure with some of the layers being less than 1 μm thick [7].…”
Section: 2deposition Pattern In the Divertormentioning
confidence: 99%
“…Computer codes are used for these calculations [51], and the best of these codes have been demonstrated accurate for RBS to at least 0.2% [46]. Computer codes for IBA have been comprehensively reviewed recently [52].…”
Section: Equationmentioning
confidence: 99%
“…A few specialized codes concern PIXE simulation [15]- [19] specifically. These codes can model simple experimental geometries, such as targets consisting of layers, and impose limitations on the type of material samples they can deal with.…”
Section: Overview Of Software For Pixe Simulationmentioning
confidence: 99%
“…Functionality for PIXE simulation has been included in Geant4 relatively recently [19] and its use has been demonstrated in the experimental context: to the best of the authors' knowledge, this is the first generalpurpose Monte Carlo system providing tools for PIXE simulation.…”
Section: Overview Of Software For Pixe Simulationmentioning
confidence: 99%